2005
DOI: 10.1161/01.res.0000175935.08283.27
|View full text |Cite
|
Sign up to set email alerts
|

Transmural Heterogeneity of Na + –Ca 2+ Exchange

Abstract: Spatial electrical heterogeneity has a profound effect on normal cardiac electrophysiology and genesis of cardiac arrhythmias in diseased hearts. The Na ؉ -Ca 2؉ exchanger (NCX) is a key linker, through Ca 2؉ signaling, between contractility and arrhythmias. Here we characterize the differential transmural expression of NCX in normal and rapid pacing-induced failing canine hearts. Significant transmural heterogeneity of NCX was present in normal hearts, as NCX current density measured at ؉80 mV was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Zygmunt et al (2000) reported an unequal distribution of NCX across the canine left ventricular wall, where peak reverse mode current is greatest in midmyocardial cells and weakest in endocardial cells. Xiong et al (2005) found greater NCX mRNA and protein in the epicardium compared to the midmyocardium and endocardium in normal canine tissue. In a separate series of experiments in guinea pig, we found that alternans prone regions (endocardium) express significantly less SERCA2a and RyR compared to alternans resistant regions (epicardium), suggesting a molecular basis for cellular alternans and specifically implicating calcium cycling proteins responsible for SR reuptake and release.…”
Section: Mechanisms Of Calcium Transient Alternans: Calcium Cyclingmentioning
confidence: 73%
“…Zygmunt et al (2000) reported an unequal distribution of NCX across the canine left ventricular wall, where peak reverse mode current is greatest in midmyocardial cells and weakest in endocardial cells. Xiong et al (2005) found greater NCX mRNA and protein in the epicardium compared to the midmyocardium and endocardium in normal canine tissue. In a separate series of experiments in guinea pig, we found that alternans prone regions (endocardium) express significantly less SERCA2a and RyR compared to alternans resistant regions (epicardium), suggesting a molecular basis for cellular alternans and specifically implicating calcium cycling proteins responsible for SR reuptake and release.…”
Section: Mechanisms Of Calcium Transient Alternans: Calcium Cyclingmentioning
confidence: 73%
“…Wan et al (36) demonstrated that myocytes isolated from guinea pig LV ENDO develop Ca 2ϩ alternans at longer BCL than EPI cells and that this difference is not related to any difference in APD. There is also growing evidence that there are differences in expression of Ca 2ϩ -cycling proteins in the three ventricular cell types (24,37,39). These transmural differences in Ca 2ϩ -cycling protein expression may explain the greater sensitivity of ENDO and MID cells to alternans (24).…”
Section: Resultsmentioning
confidence: 99%
“…20 As shown in Figure 5, the expression of NCX1 protein and membrane current through the NCX1 (INCX) were enhanced in the MI group. In the MI+MMP-1 group, INCX was significantly reduced to a similar level as in the Normal group, but no significant decrease in mRNA encoding NCX1 was found.…”
Section: Increased Myocyte Shortening By Mmp-1 Plasmid Dnamentioning
confidence: 86%